2003
DOI: 10.1038/sj.ejcn.1601816
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrition on cognitive function in a group of elderly, independently living people

Abstract: Objective: To study the differences in cognitive status with respect to food habits and energy and nutrient intake in a group of non institutionalised, elderly people. Design: Prospective study. Setting: The study subjects were independently living, elderly people who spent some of their time at day centres in the Comunidad de Madrid (the Madrid region). The study centres were selected by the Madrid City Hall. Subjects: The study included 168 elderly people aged 65-90 y. All accepted the invitation to particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 13 publications
4
49
2
2
Order By: Relevance
“…In 168 elderly subjects whose dietary intake was monitored using a food record for seven consecutive days individuals with satisfactory intellectual function (mini mental state examination >28) were generally found to have a greater intake than those with cognitive impairment (Requejo et al 2003). These findings confirm earlier data from Ortega et al (1997).…”
Section: Effect Of Nutritional Support On Cognitive Functionsupporting
confidence: 81%
“…In 168 elderly subjects whose dietary intake was monitored using a food record for seven consecutive days individuals with satisfactory intellectual function (mini mental state examination >28) were generally found to have a greater intake than those with cognitive impairment (Requejo et al 2003). These findings confirm earlier data from Ortega et al (1997).…”
Section: Effect Of Nutritional Support On Cognitive Functionsupporting
confidence: 81%
“…A Spanish study also showed that elderly people with preserved cognitive functions generally had a better diet, including a greater intake of fish (Requejo et al, 2003). Since there seems to be a doseresponse relationship, more research is needed to determine the optimal frequency of fish consumption associated with a lower risk of dementia and other health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This section summarizes the findings from three (retrospective and prospective) longitudinal studies [2,3] and five cross-sectional studies [4][5][6][7][8] that examined the association between the dietary intake levels of B vitamins and cognitive function or the risk of age-related neurodegenerative diseases. The report included all populations for longitudinal studies, whereas only noninstitutionalized or free-living populations were included for cross-sectional studies in order to assess their "usual" dietary intake levels.…”
Section: Association Of Dietary Intake Levels Of B Vitamins With Age-mentioning
confidence: 99%
“…Three studies associated participants' dietary intake levels of vitamin B 12 with their cognitive function scores [3,5,8]. One additional study compared the dietary intake levels of vitamin B 12 in participants with Alzheimer's disease and in normal participants [7].…”
Section: Cross-sectional Studies Vitamin B 12 Intakementioning
confidence: 99%
See 1 more Smart Citation